2021
DOI: 10.3389/fphar.2021.651156
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Chelates Excessive Iron and Prevents the Formation of Amyloid-Beta Plaques in the Hippocampus of Iron-Overloaded Mice

Abstract: Metal chelating agents are antioxidant agents, which decrease the reductive potential and stabilize the oxidized metal ion form. In this study, we evaluated the naringin capacity in chelating iron and preventing amyloid-beta plaque formation in the hippocampus of iron-overloaded mice. Thirty-five NMRI male mice (8–10 weeks old) were provided. The mice were classified into five groups. Iron dextran was administered as i.p. injection (100 mg/kg/day) four times a week for four subsequent weeks. The treated groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Then, sections were rinsed with distilled water three times and the nuclei were counterstained with nuclear fast red (Beyotime Biotechnology, China). Finally, the sections were photographed under a fluorescence microscope at 400× and 100× magnification (Nikon, Japan) (Jahanshahi et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, sections were rinsed with distilled water three times and the nuclei were counterstained with nuclear fast red (Beyotime Biotechnology, China). Finally, the sections were photographed under a fluorescence microscope at 400× and 100× magnification (Nikon, Japan) (Jahanshahi et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both Hesperidin and coumarin have antioxidant activity and can decrease free radical production (Lin et al, 2008;Nakao et al, 2011). Some natural products have metal chelation and antioxidant activities such as citrus fruits, hesperidin, coumarin, naringin, coumarin, resveratrol, quercetin, naringin, and silymarin (Mokni et al, 2007;Cui et al, 2014;Dong et al, 2014;Wang et al, 2014;Ebrahimzadeh et al, 2015Ebrahimzadeh et al, , 2016Filipsky et al, 2015;Khalili et al, 2015a;Zou et al, 2016;Chen et al, 2018;Jahanshahi et al, 2021). Our results show that hesperidin and coumarin have potential iron chelation activities.…”
Section: Discussionmentioning
confidence: 56%
“…Tocotrienol-rich fraction, as a natural product, had some dose-dependent effects on serum total cholesterol and LDL-cholesterol (Qureshi et al, 2002). Our previous study demonstrated that naringin could chelate excessive iron from the brain tissues and serum of the iron-overloaded mice (Jahanshahi et al, 2021). Iron accumulation in the brain occurs with aging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations